2018
DOI: 10.1002/ecy.2160
|View full text |Cite
|
Sign up to set email alerts
|

Seed banks of native forbs, but not exotic grasses, increase during extreme drought

Abstract: Extreme droughts such as the one that affected California in 2012-2015 have been linked to severe ecological consequences in perennial-dominated communities such as forests. In annual communities, drought impacts are difficult to assess because many species persist through facultative multiyear seed dormancy, which leads to the development of seed banks. Impacts of extreme drought on the abundance and composition of the seed banks of whole communities are little known. In 80 heterogeneous grassland plots where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 71 publications
(136 reference statements)
12
48
1
Order By: Relevance
“…Not all findings are consistent across studies though. In contrast to our results, LaForgia et al () found greater drought tolerance for Bromus diandrus than Bromus madritensis and Bromus hordeaceus . Our data may only represent local patterns, and so reinforce the value of research from multiple sites in helping resolve how habitat and species characteristics shape drought and fire responses.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Not all findings are consistent across studies though. In contrast to our results, LaForgia et al () found greater drought tolerance for Bromus diandrus than Bromus madritensis and Bromus hordeaceus . Our data may only represent local patterns, and so reinforce the value of research from multiple sites in helping resolve how habitat and species characteristics shape drought and fire responses.…”
Section: Discussioncontrasting
confidence: 99%
“…We also cannot rule out the possibility that responses were contingent on conditions specific to the fire year, although total precipitation immediately after fire (2013–2014) was closer to average than for any other growing season in the study (Figure ). Still, our findings are consistent with declines in both above‐ground cover and seed banks of exotic grasses in other California grasslands during the recent drought, paralleled by increases in some native forbs (Harrison, Gornish, & Copeland, ; LaForgia, Spasojevic, Cse, Latimer, & Harrison, ). Similarly, in a predominately native California grassland the recent drought corresponded with disproportionate declines of the most common species and compensatory increases in some rarer competitors (Prugh et al, ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…They found that invasive species responded more strongly to carbon dioxide enrichment and elevated temperature (and did not respond significantly to nitrogen deposition and increased precipitation), indicating that the problems caused by invasive plant species are likely to get worse under a changing climate. This study suggested that drought may be detrimental for invasive species, as did a seedbank study in Californian annual grasslands, which found that seeds of exotic annual grasses declined whilst native annual forbs increased 15 . Invasive species have very large impacts on grassland communities in some parts of the world, meaning that understanding and predicting these impacts is a priority.…”
Section: Threats To Grasslandssupporting
confidence: 50%